2020
DOI: 10.1155/2020/1536714
|View full text |Cite
|
Sign up to set email alerts
|

High-Dose Inhaled Nitric Oxide as Adjunct Therapy in Cystic Fibrosis Targeting Burkholderia multivorans

Abstract: Background. Individuals with cystic fibrosis (CF) have persistent lung infections, necessitating the frequent use of antibiotics for pulmonary exacerbations. Some respiratory pathogens have intrinsic resistance to the currently available antibiotics, and any pathogen may acquire resistance over time, posing a challenge to CF care. Gaseous nitric oxide has been shown to have antimicrobial activity against a wide variety of microorganisms, including common CF pathogens, and offers a potential inhaled antimicrobi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 22 publications
0
19
0
4
Order By: Relevance
“…More recently, nitric oxide at a high dose (160–200 ppm) has demonstrated broad antimicrobial activity on bacteria and viruses such as severe acute respiratory syndrome coronavirus (SARS-CoV-1), the virus that caused severe acute respiratory syndrome in 2003. 1 3 …”
mentioning
confidence: 99%
“…More recently, nitric oxide at a high dose (160–200 ppm) has demonstrated broad antimicrobial activity on bacteria and viruses such as severe acute respiratory syndrome coronavirus (SARS-CoV-1), the virus that caused severe acute respiratory syndrome in 2003. 1 3 …”
mentioning
confidence: 99%
“…Over the past two years, at Massachusetts General Hospital (Boston, MA), we have treated a teenage patient with 46-intermittent inhalation of 160 ppm NO for antibiotic resistant Burkholderia multivorans lung infection in the setting of cystic fibrosis. No adverse events or delivery system failures were observed, respiratory symptoms of the patient improved and the antibiotic pattern of the Burkholderia multivorans changed to allow common antibiotic coverage (i.e., Bactrim and Levofloxacin) [ 16 ]. Additionally, inhaled NO therapy has also shown to be a potent anti-inflammatory agent, reducing lung thrombosis after lung transplant [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…In K. pneumoniae infected mice, inhaling NO at lower oxygen concentration also resulted in a 5 to 10-fold reduction of CFU in BALF and lung tissues (Sun et al 2006 ). Similar bactericidal effects were also observed in CF patients, where case studies showed that intermittent administrations of 160 ppm NO significantly reduced CFU of P. aeruginosa , S. aureus , and B. multivorans in CF patients that are resistant to multiple antibiotics (Deppisch et al 2016 ; Bartley et al 2020 ). As such, inhalation of NO may improve the therapy of chronic lung infections in CF patients, particularly for those suffering from MDR pathogens.…”
Section: No Delivery In Vivomentioning
confidence: 99%